2011
DOI: 10.1097/ta.0b013e3182092ff8
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Radiation Exposure During the Initial Evaluation for Blunt Trauma

Abstract: Thyroid doses in 71% of study patients fell within the dose range historically correlated with an increased risk of thyroid cancer and whole body effective doses fell within the range of historical doses correlated with an increased risk of all solid cancers and leukemia. Selective scanning of body areas as compared with whole body scanning results in a statistically significant decrease in all doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 24 publications
1
28
0
2
Order By: Relevance
“…First, advanced imaging technology has been an important driver for the escalating cost of health care (8,9). Second, CT uses ionizing radiation that could potentially be harmful in the long term, especially for children (3,7,(10)(11)(12)(13).…”
Section: Methodsmentioning
confidence: 99%
“…First, advanced imaging technology has been an important driver for the escalating cost of health care (8,9). Second, CT uses ionizing radiation that could potentially be harmful in the long term, especially for children (3,7,(10)(11)(12)(13).…”
Section: Methodsmentioning
confidence: 99%
“…32,33 Often in a trauma evaluation cervical spine CT is part of a larger evaluation in which both head and chest imaging are considered and thus the cumulative radiation effects must be considered. 34 With the above data and reports of cervical spine CT rates increasing in some areas, despite a simultaneous downward trend in other types of scans, clinicians must continue to address the challenge to reduce unnecessary scans. 15 This model suggests that unless the probability of cervical spine injury is high, clinical clearance or screening radiographs should predominate the current management strategies when radiation risk is considered.…”
Section: Discussionmentioning
confidence: 94%
“…Broder et al reported that over 6 years the use of abdominal CT increased by 49%, while chest CT imaging increased by 435% in a pediatric population [12]. This increased use led to identification of findings that would have previously been missed [12,13]. OPTX are identified in 2% to 15% of patients undergoing CT scan [14][15][16].…”
Section: Discussionmentioning
confidence: 98%